FAKTOR-FAKTOR YANG MEMPENGARUHI KEMANDIRIAN DAERAH KABUPATEN TELUK BINTUNI TAHUN 2010-2015 - Manasep Orocomna; Bonifasia Elitha Bharanti; Paulus K. Allo Layuk (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2017)
Economic development is an attempt to support one of national priorities, namely accelerate economic recovery and strengthen the sustainable economic development system based on the people's system. These priorities determination base on issue and facing challenges and the policy in economic development in short term and medium term as well (Propenas 2012-2014). This study attempts to analyze the fiscal dependency level of Teluk Bintuni regency with the central government viewed from local fiscal decentralization degrees. Second, to analyze the influence of vehicle taxes on local revenue, which is regional potency to develop local fiscal independency. This research uses secondary data (time series) from year 2010 to 2014. This data analyzed in linear regression. Based on the calculation the transfer variable (x1) shows calculated t of 3,659; the number of vehicles wheels 4 or more (x2) shows calculated t of 3,595; the number of vehicles wheels 2 (x3) shows calculated t of 4,140; and regional investment (x4) shows calculated t of 4,595; with the significance level smaller than 0,05 so it can be concluded that the variables partially free and significant impact on the local revenue Teluk Bintuni regency. The f value of 23,468 (23,468 > 9,12) with the significance of 0,000 ( 0,000 < 0,05 ) that can be concluded that four independent variables which are the transfer, the number of vehicles wheels 4 or more, the number of vehicles wheels 2, and investment, together affecting the local revenue of Teluk Bintuni regency. Local revenue Teluk Bintuni regency can be explained by variation of the four independent variables: the transfer, the number of vehicles wheels 4 or more, the number of vehicles wheels 2, and local investment of 96,9 percent. Keyword: regional independency, tax, retribution, gross domestic regional product